Living the crisis in Latin America.: Comparative Study between Jiutepec, State of Morelos, Mexico and the City of Villa María, Province of Córdoba, Argentina, 2001-2018 - Crespo, Maria Victoria (Universidad Nacional de Villa María, 2020)
This article analyzes and compares two development experiences in Latin American contexts of crisis. It presents the outcome of a comparative research between two Latin American municipalities: The Municipality of Jiutepec, State of Morelos, Mexico, and the City of Villa María, Province of Córdoba, in Argentina. It considers their twentieth century trajectories as well as their experiences during the contemporary crisis, defined in the period that spans from 2001 to 2019. The core of the article establishes a contrast between two divergent development models implemented in these two Latin American cities: one based on autonomy and the other in heteronomy. Through in-depth interviews, it seeks to identify the positioning, experiences and social practices of social actors in the context of the contemporary crisis, what we may call a “crisis habitus”. It tackles questions such as the conceptualization, temporal cuts and specific dates that social actors associate to the crisis, as well as the strategies that they put to play to confront the crisis. Finally, the article reflects on the horizons of expectations and opportunities that emerge in the midst of crises.